1992
DOI: 10.1002/jbmr.5650070207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of swimming on prednisolone-induced osteoporosis in elderly rats

Abstract: We investigated the possible ameliorating and preventive effect of swimming on prednisolone-induced osteoporosis in elderly rats. A total of 48 female Sabra strain rats were randomly assigned to the following groups and treatments: (1) control (C), (2) swimming (S), (3) prednisolone-treated (CP), and (4) swimming + prednisolone (SP). An additional 8 rats were sacrificed and examined at the onset of the study. Groups C and S were sham injected; groups CP and SP were injected with prednisolone (Ultracorten), 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
(2 reference statements)
1
9
0
Order By: Relevance
“…6,[10][11][12][13][14] No significant difference in the maximum breaking force of the lumbar vertebral body was described among the exercise and control groups in mature osteopenic rats submitted to the strong physical activity, and that the beneficial effects of running exercise on weight-bearing bones with estrogen deficiency and inadequate calcium intake are reached only when an optimal level of exercise is applied. 47 Previous studies showed that different endurance training intensity levels led to differences in body weight and bone parameters of rats.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…6,[10][11][12][13][14] No significant difference in the maximum breaking force of the lumbar vertebral body was described among the exercise and control groups in mature osteopenic rats submitted to the strong physical activity, and that the beneficial effects of running exercise on weight-bearing bones with estrogen deficiency and inadequate calcium intake are reached only when an optimal level of exercise is applied. 47 Previous studies showed that different endurance training intensity levels led to differences in body weight and bone parameters of rats.…”
mentioning
confidence: 82%
“…13 Swimming may have a beneficial effect on BMD compared to the controls for elderly animals with induced osteoporosis. 14 On the other hand, weightlessness or skeletal unloading such as swimming may not have an equivalent beneficial effect on BMD when compared to weighted training, 10 or could lead to bone loss in rats with hypertension-induced osteoporosis 12 and healthy scuba-divers. 6 The prescription of water activities has been traditionally adopted as a preventive tool for bone health in the elderly, 15,16 but studies demonstrated that overtraining and compulsive exercise could lead to pronounced loss of bone minerals.…”
Section: Introductionmentioning
confidence: 99%
“…At 7 weeks after surgery, bone loss was confirmed, and the trabecular bone in the femoral neck between the SHAM and OVX groups was compared using Micro-CT. One week later, the rats were assigned to the following treatments: SHAM and OVX groups (corn oil containing a 3:2 mixture of DMSO and ethanol), OVX + E2 (0.5 mg/kg E2 p.o., three times a week), and OVX + API (10 mg/kg API p. o., three times a week), and fed a 5L79 diet for 15 weeks. The API and E2 (Sigma-Aldrich, St. Louis, MO, USA) were each dissolved in a mixture of DMSO and ethanol; a 100 μg/ml working dilution was created using corn oil immediately prior to administration (Gallo et al, 2005;Mosekilde, 1995;Swissa-Sivan et al, 1992;Zanoli et al, 2000). Body weight and food intake were measured once a week during the experimental period.…”
Section: Animalsmentioning
confidence: 99%
“…Weight-bearing exercise is not the only exercise that is good for the skeletal system; endurance swimming-a non-weight-bearing, moderate-intensity aerobic exercise-has also been shown to benefit calcium and bone metabolism by increasing intestinal calcium absorption [15], BMD [16], bone growth [17], and bone strength [18]. In addition, swimming is usually recommended for postmenopausal osteoporotic patients unable to perform weight-bearing exercise because they are overweight, have a joint injury, or are at risk of fracture [19].…”
Section: Introductionmentioning
confidence: 99%